Автодинные ЧМ-локаторы КВЧ-диапазона с непрерывным излучением - Smolsky, S. M.; Votoropin, S. D.; Savkov, N. N.; Pleshcheev, A. A.; Trofileev, A. A.; Ostapenkov, P. S.; Fedotov, A. M. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
The paper analyzes frequency-modulated (FM) autodyne short-range radar systems (SRRS) operating at small distances, which are used in both military and civilian applications and require collaboration between radar specialists and experts in microwave device microelectronics. The processes in FM SRRS, the autodyne effect, and parasitic amplitude modulation are studied. Several real designs are experimentally described, and their investigation confirms the theoretical conclusions.